Interrelationships Within the Bacterial Flora of the Female Genital Tract - Henry J. Carson; Paul G. Lapoint; Gilles R. G. Monif (Hindawi Limited, 1997)
Analysis of 240 consecutive vaginal swabs using the compatibility profile technique revealed that only 2 bacteria have the ability to be a sole isolate and as such a candidate to be a major aerobic regulator of the bacterial flora of the female genital tract (BFFGT). Compatibility profiles of Lactobacillus and Gardnerella vaginalis have shown that these organisms shared compatibility profiling for the majority of the normal bacterial constituents of the female genital tract. Dominance disruption appears to come from the addition of compatible co-isolates and presumed loss of numerical superiority. These phenomena appear to be the keys to reregulation of BFFGT. Lactobacillus appears to be the major regulator of both G. vaginalis and anaerobic bacteria. When additional organisms are added to the bacterial flora, they may add to or partially negate the inhibitory influence of Lactobacillus on the BFFGT. Inhibitor interrelationships appear to exist between coagulase-negative staphylococci and Staphylococcus aureus and the group B streptococci (GBS) and other beta hemolytic streptococci. Facilitating interrelationships appear to exist between S. aureus and the GBS and selected Enterobacteriaceae.